Penyuluhan Pembentukan UMKM dan Pengelolaan Keuangan - Harry Barli; Ambarwati Ambarwati; Fina Ratnasari (Abdimisi, 2021)
Financial management is a basic thing that must be owned by MSME actors to be able to maintain the continuity of their business. However, there are still many business actors who have not implemented good financial management. This community service (PKM) collaborates with business owners Pempek Delish Yogyakarta with the aim of providing counseling on the formation of MSMEs and business financial management. This PKM activity is carried out through a zoom meeting with implementation methods in the form of counseling, lectures, and online discussions. It is hoped that with virtual (online) guidance by PKM implementing lecturers from Pamulang University regarding the formation of MSMEs and financial management, it will be able to increase the sustainability of Pempek Delish's business and in the end it will bring benefits to various parties, not only business owners, but also academics. and the rest of the business world.